2022
DOI: 10.1177/11795549221137135
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data of Trifluridine/Tipiracil for Patients With Advanced Gastric Cancer: A Multi-Institutional Retrospective Study

Abstract: Background: A trial with trifluridine/tipiracil (FTD/TPI) versus placebo in patients with heavily pretreated metastatic gastric cancer showed that FTD/TPI is effective with manageable toxicity in these patients. However, real-world data on the effects of FTD/TPI in patients with advanced gastric cancer (AGC) are limited. Methods: We retrospectively collected and analyzed the clinicopathological data of patients with AGC who received FTD/TPI monotherapy at our institutions (Kobe City Medical Center General Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In our patient, the HER2 status on immunohistochemistry was 3+, consistent with the results of previous trials [4,12]. Matsumoto et al [13] suggested that the pre-administration of immune checkpoint inhibitors (ICI) and a sufficient trastuzumab-free interval are favorable prognostic factors for T-Dxd efficacy. While predicting treatment response with T-Dxd administration would be a valuable clinical benchmark, it has not yet been established.…”
Section: Case Reports In Oncologysupporting
confidence: 90%
“…In our patient, the HER2 status on immunohistochemistry was 3+, consistent with the results of previous trials [4,12]. Matsumoto et al [13] suggested that the pre-administration of immune checkpoint inhibitors (ICI) and a sufficient trastuzumab-free interval are favorable prognostic factors for T-Dxd efficacy. While predicting treatment response with T-Dxd administration would be a valuable clinical benchmark, it has not yet been established.…”
Section: Case Reports In Oncologysupporting
confidence: 90%
“…According to the ATTRACTION-2 trial, the long-time survival from nivolumab treatment was unsatisfactory, which suggests that the majority of gastric cancer patients may not benefit from nivolumab monotherapy [ 16 ]. Matsumoto et al reported that the pre-administration of immune checkpoint inhibitors maybe the key to achieving a favorable prognosis and enhancing the efficacy of TDXD [ 17 ]. In the present case, nivolumab was administrated prior to TDXD and was able to achieve a stable disease control for more than 1 year and 6 months.…”
Section: Discussionmentioning
confidence: 99%